Reading Reconstruction : Sherwood Bonner and the Literature of the Post-Civil War South - McKee, Kathryn B. (Book collections on Project MUSE., 2019)
"Kathryn B. McKee's Reading Reconstruction situates the Mississippi writer Katharine Sherwood Bonner McDowell (1849-1883) as an important cultural observer of the 1870s and 1880s who channeled into her fiction and nonfiction the discord and uneasiness of the Reconstruction era. In works like the novel Like unto Like--as well as her regional stories and travel writing--Bonner engaged questions about shifting definitions of citizenship, questioned the evolving rhetoric of postwar reconciliation, and embraced the disruptive potential of humor to unsettle conventional domestic scenarios and gender roles. McKee shows how Bonner's works rehearsed the roles expected of white southern women, both at home and abroad, while also presenting characters who knowingly violate those norms and then confront the consequences of their actions. Her fiction also routinely undermined the social prerogatives of manhood and whiteness by inventing landscapes in which they exercised limited power. But despite these overt challenges to the period's dominant narratives, Bonner's writing frequently retreated to the familiar, comfortable ground of racial supremacy, if not patriarchy, before situations veered in the direction of lasting change. By contextualizing the work of an astute social commentator from the post-Civil War South, Reading Reconstruction offers a long overdue reassessment of Sherwood Bonner's place in American literary history by challenging traditional readings of postbellum southern literature"--